Contribution of Ali Hasjmy's Legacy of Thought to Aceh Islamic Education - Arfan, Fahmi; Nirwana, Andri; Fuadi, Muhammad; Fadli, Nazar; Ana, Ayu Sahfitri (Universitas Muhammadiyah Surakarta, 2024)
Ali Hasjmy is a writer, cleric, and key figure in advancing education in Aceh. His educational philosophy covers the purpose of education, distinctions between teaching and education, critique of secularism, and the importance of religious instruction. This research, based on a literature review, shows that for Hasjmy, education nurtures faith, knowledge, and virtuous deeds, aiming to produce people devoted to God, knowledgeable, morally upright, and ready to defend the oppressed. Religious education, he argued, is vital, not just for knowledge, but for practical application in daily life. Hasjmy opposed educational secularism, insisting that education should strengthen faith while equipping students with practical skills for societal development, particularly in agriculture, industry, and mining. His ideas remain relevant, symbolized by the decree No. 90 of 1960, which established September 2 as Aceh's Education Day. He envisioned Aceh as a hub of Islamic knowledge and culture and spearheaded the Darussalam Educational Concept to improve education. His efforts laid the foundation for the continued growth of education in Aceh, creating a well-integrated system where the younger generation could advance, benefiting from the groundwork laid by previous generations.